Reflection on development of careful, creative and critical thought according to the philosophy of Matthew Lipman; a proposal for inclusion in basic education and paintings in their steps fractals (2020)
ABSTRACT: To satisfy the imperative need for developing life skills in basic education students throughout the country, it is important to think about continue educational inclusion, which is to be understood as the idea of Education for All. Education for all should satisfy the basic needs of learning while developing the individual and social welfare of each student. From this perspective, it is necessary to reflect on how to make students citizens who make decisions and assume consequences, so that they can act with critical judgment. For this, it is necessary to inspect and reconstruct the essence of critical, creative and careful thinking, the essence of learning to think.